2022
DOI: 10.1002/mp.15502
|View full text |Cite
|
Sign up to set email alerts
|

A novel simulation‐driven reconstruction approach for x‐ray computed tomography

Abstract: Radiation dose reduction is critical to the success of x-ray computed tomography (CT). Many advanced reconstruction techniques have been developed over the years to combat noise resulting from the low-dose CT scans. These algorithms rely on accurate local estimation of the image noise to determine reconstruction parameters or to select inferencing models. Because of the difficulties in the noise estimation for heterogeneous objects, the performance of many algorithms is inconsistent and suboptimal. Here, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Based on extensive experiments, we found that the non‐local means (NLM) filter, Γ h , performs the best in removing correlated noise in CT images, where h specifies the “degree of smoothing.” 30 The parameter h , which controls the sizes of the similarity‐window and the search‐window, is driven by the standard deviation, σ, in the image. Our previous study has shown that the noise in d ( x , y ) can be accurately estimated by a noise‐insertion process when the scan data is available 26 . It has been demonstrated that the noise estimated with such approach is accurate not only on a global scale, but also in local regions.…”
Section: Generation Of Synthesized High Dose Imagesmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on extensive experiments, we found that the non‐local means (NLM) filter, Γ h , performs the best in removing correlated noise in CT images, where h specifies the “degree of smoothing.” 30 The parameter h , which controls the sizes of the similarity‐window and the search‐window, is driven by the standard deviation, σ, in the image. Our previous study has shown that the noise in d ( x , y ) can be accurately estimated by a noise‐insertion process when the scan data is available 26 . It has been demonstrated that the noise estimated with such approach is accurate not only on a global scale, but also in local regions.…”
Section: Generation Of Synthesized High Dose Imagesmentioning
confidence: 99%
“…Our previous study has shown that the noise in d(x, y) can be accurately estimated by a noise-insertion process when the scan data is available. 26 It has been demonstrated that the noise estimated with such approach is accurate not only on a global scale, but also in local regions. The accuracy of the noise estimation is not influenced or biased by the presence of complex anatomical structures.…”
Section: Algorithm Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Deep learning (DL) has been explored in recent years for CT noise-reduction as part of the image reconstruction or the post-processing. [14][15][16][17][18][19][20][21] When proper training datasets are used, DL has shown significant noise-reduction capability while preserving the FBP-like peak-frequency in NPS. In DL, the production of the ground-truth images (GTI) is critical, since DL relies heavily on large training datasets to achieve high accuracy.…”
Section: Introductionmentioning
confidence: 99%